Case report: Delayed outflow obstruction of a DVA: A rare complication of brainstem cavernoma surgery - Agyemang, Kevin; Gómez Rodríguez, Rony; Rocha Marussi, Victor Hugo; Marte Arias, Sally Allinson; Feliciano Vilcahuaman Paitań, Alexander; Campos Filho, José Maria; Chaddad-Neto, Feres (Frontiers in Neurology, 2023)
Introduction Developmental venous anomalies (DVAs) are considered variants of normal transmedullary veins. Their association with cavernous malformations is reported to increase the risk of hemorrhage. Expert consensus recommends meticulous planning with MR imaging, use of anatomical “safe zones”, intraoperative monitoring of long tracts and cranial nerve nuclei, and preservation of the DVA as key to avoiding complications in brainstem cavernoma microsurgery. Symptomatic outflow restriction of DVA is rare, with the few reported cases in the literature restricted to DVAs in the supratentorial compartment. Case We present a case report of the resection of a pontine cavernoma complicated by delayed outflow obstruction of the associated DVA. A female patient in her 20's presented with progressive left-sided hemisensory disturbance and mild hemiparesis. MRI revealed two pontine cavernomas associated with interconnected DVA and hematoma. The symptomatic cavernoma was resected via the infrafacial corridor. Despite the preservation of the DVA, the patient developed delayed deterioration secondary to venous hemorrhagic infarction. We discuss the imaging and surgical anatomy pertinent to brainstem cavernoma surgery, as well as the literature exploring the management of symptomatic infratentorial DVA occlusion. Conclusion Delayed symptomatic pontine venous congestive edema is extremely rare following cavernoma surgery. DVA outflow restriction from a post-operative cavity, intraoperative manipulation, and intrinsic hypercoagulability from COVID-10 infection are potential pathophysiological factors. Improved knowledge of DVAs, brainstem venous anatomy, and “safe entry zones” will further elucidate the etiology of and the efficacious treatment for this complication.